Answer:
-7
Step-by-step explanation:
77 ÷ (-11) = -7
Answer:
x = 5
Step-by-step explanation:
√(2x − 1) + 2 = x
√(2x − 1) = x − 2
2x − 1 = (x − 2)²
2x − 1 = x² − 4x + 4
0 = x² − 6x + 5
0 = (x − 1) (x − 5)
x = 1 or 5
Check for extraneous solutions.
√(2(1) − 1) + 2 = 1
√(1) + 2 = 1
3 = 1
No solution
√(2(5) − 1) + 2 = 5
√(9) + 2 = 5
5 = 5
x = 5
Answer:
-7
Step-by-step explanation:
To find y, follow these steps:
4y - 2 (1 - y) = -44
First, distribute the -2 into the parenthesis:
4y - 2 + 2y = -44
The reason the 2y is positive is due to the fact that negative and negative cancel each other out and form a positive.
Now, combine like terms:
6y - 2 = -44
To get y, you need to isolate it from the constants. In order to do so, do the inverse relationship for the constant -2. To do this, add 2 to -44:
6y = -42
Now, divide six on both sides. You divide because six is currently being multiplied with y. Keep in mind that the 42 is still negative!
y = -7
Hope this helps!
Answer:
No solution
Step-by-step explanation:
Not sure tbh